Ikatan Elektroda Pembumian Petir untuk Memperbaiki Resistansi Pembumian Instalasi Listrik di Laboratorium Instalasi Listrik Politeknik Negeri Bandung - Sunarto Sunarto (SEMNASTERA (Seminar Nasional Teknologi dan Riset Terapan), 2020)
For human safety and security against the dangers of electric shock, a grounding system is required in electrical installations. The value of the earth resistance should be as small as possible according to the required PUIL 2000 not to be more than 5 Ohm. If the earthing that has been installed turns out that the resistance value exceeds the required value, it is necessary to improve the earth's resistance value. One of the easiest ways to improve the earth's resistance value is to install several earth points that are connected (parallel). The value of earthing resistance at the Bandung State Polytechnic (Polban) Electrical Installation Laboratory based on the measurement results is 10.3 Ohm. This value far exceeds the value required by PUIL 2000, therefore it needs to be improved. In the vicinity of the Politeknik Negeri Bandung Electrical Installation Laboratory building, there is an earthing of electrode rods from the old lightning distribution installations no longer used. The rod electrodes can be used to improve or reduce the earth's resistance value. Therefore, through Beginner research, the above problems become the subject of research with the improving the earthing resistance value in the Polban Electrical Installation Laboratory so that it can improve human security and safety against the dangers of electric shock currents. In this study, using an experimental method to obtain data, namely by measuring the earthing resistance value of an installed electrical installation using an Earth Tester. Because the earthing resistance value exceeds the required value, it needs to be repaired by connecting some of the electrode points of the lightning rods no longer used with the grounding of the installed electrical installation.